Treatment of posterior crossbite in mixed dentition with a removable appliance: Reports of cases - Cunha, Robson Frederico [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Costa, L.; Abreu, M. G. de (Amer Soc Dentistry Child, 1999)
A posterior crossbite malocclusion is defined as an abnormal buccolingual relationship. One or more maxillary teeth improperly occludes with one or more mandibular teeth in centric relation. This alteration develops early and is seldom self-correcting. This study is a report of the benefits of treating posterior crossbite malocclusions in mixed dentitions using removable appliances.
Keywords: posterior crossbite; removable appliance